1986
DOI: 10.1007/bf01299810
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron microscopic localization of HLA-DR antigen in control small intestine and colon and in inflammatory bowel disease

Abstract: We have elucidated the distribution of I2 (HLA-DR) antigen in control and inflammatory bowel disease specimens, using immunoelectron microscopic methods. Control small intestinal epithelium and inflammatory bowel disease epithelium expressed 12 antigen, while control colonic epithelium did not. I2 expression by enterocytes was more frequent on the lateral and basal surface than on the microvillus surface. Two of three M cells in control ileum expressed I2 antigen. I2-positive intraepithelial lymphocytes were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 36 publications
3
29
0
2
Order By: Relevance
“…A first striking feature observed was the polarized nature of class II HLA‐DR expression, with surface expression almost entirely restricted to the basolateral surface. This distribution is consistent with the site of T‐cell/epithelial cell interaction in vivo , and has been reported in some electron microscope studies of HLA distribution, 28 , 29 as well as in a recent study on T84 cells 9 . However, other studies using light immunohistochemistry have reported HLA‐DR on both surfaces of the intestinal epithelium, and this question clearly needs further study to resolve these apparent contradictions.…”
Section: Discussionsupporting
confidence: 87%
“…A first striking feature observed was the polarized nature of class II HLA‐DR expression, with surface expression almost entirely restricted to the basolateral surface. This distribution is consistent with the site of T‐cell/epithelial cell interaction in vivo , and has been reported in some electron microscope studies of HLA distribution, 28 , 29 as well as in a recent study on T84 cells 9 . However, other studies using light immunohistochemistry have reported HLA‐DR on both surfaces of the intestinal epithelium, and this question clearly needs further study to resolve these apparent contradictions.…”
Section: Discussionsupporting
confidence: 87%
“…How is the inflammatory process in disorders like CD–which presumably originate in the mucosa 128 –directed to the ENS? A number of findings indicate that enteric glia may be instrumental to attract immune cells: lymphocytic infiltrates in the ENS of CD patients are associated with glial major histocompatibility complex (MHC) class II expression, 129–131 and ultrastructural studies have revealed close contacts between CD45RO + T‐cells and MHC II‐expressing glial cells in the ENS of these patients, 131 strongly suggesting functional glia–lymphocyte interactions. Regularly, glial MHC II expression and lymphocytic infiltration of the ENS were accompanied by signs of neuronal damage 131 …”
Section: Functional Interactions Between Glia and Immune Cells In Thementioning
confidence: 99%
“…EGCs share this antigen-presenting capability as demonstrated in (GFAP-HA ϫ HA-TCR)F1 double transgenic mice. Surface MHC class II molecules are profoundly upregulated during Crohn's disease (Hirata et al, 1986;Geboes et al, 1992). Axonal abnormality and necrosis of enteric neurons (Dvorak and Silen, 1985) are strongly predictive of disease recurrence in noninflamed Crohn's disease tissues and are often associated with T-cell infiltration of neuronal plexi in a fashion that may be modeled using (GFAP-HA ϫ HA-TCR)F1 double transgenic mice (D'Haens et al, 1998;Geboes and Collins, 1998).…”
Section: Potential Mechanisms For Enteric Glial Cell Ablation and Dysmentioning
confidence: 99%